188 A REVIEW OF THE REABLEMENT PROGRAM WHICH INCLUDES THERAPY ASSISTANTS WITHIN THE AMBULATORY HUB. (25th October 2022) - Conaty, J; Smith, B; Sweeney, M
Abstract: Background: The Ambulatory Hub for the older person commenced in May 2021 in line with the Enhanced Community Care Implementation Guidance documents. From a client and carer perspective, the hub provides a single point of access and a co-ordinated approach to the client's care needs with a focus on frailty. The Reablement service is provided alongside the Hub team providing a specialist Occupational Therapy and Physiotherapy geriatric assessment. Depending on the outcome of the assessment and needs identified, the client can avail of the Reablement program. Each patient will have an individualised therapy program which is carried out by the therapy assistants in the client's home. The Reablement program aims to provide care in line with the "Right Care, Right Place, Right Team, Right Time" ethos. Methods: The charts of 20 clients who completed the Reablement program were reviewed. The data collected included the number of visits by the Occupational Therapist, Physiotherapist and therapy assistants. Feedback from the client and their family was sought and documented. Results: The results showed that clients received on average 4 Occupational Therapy and 4 Physiotherapy sessions each. The therapy assistants provided on average 15 visits per client to support the implementation of specialist programs developed by the therapy team. The feedback from clients and family was very positive and the following feedback was received "A program like this is a great initiative", " It Improved my confidence", "I'm able to cook my meals for myself again" Conclusion: The Reablement program with the support of therapy assistants has led to a patient centred service and co-ordinated approach to the care of the client with increased client compliance. A similar service was not available in the community previously. The Reablement program has reduced the need for inpatient reablement beds which was previously the pathway of care for these clients in the community.